THE INFLUENCE OF PRICE, SERVICE QUALITY AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY OF PT. PUTRA PELANGI PERKASA TAJUR BOGOR - Hanipah, Imanda; Ismartaya, Ismartaya; Silaningsih, Endang (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aimed to investigate the influence of customer satisfaction, service quality, and price on customer loyalty. This quantitative study surveyed one hundred people with a non-probability sample procedure grounded in purposive sampling. This study discovered a significant positive correlation between competitive price, high-quality service, and customer satisfaction and consumer loyalty. To optimize profit amidst competitive market dynamics, enhance customer loyalty, and successfully manage risk, firms must possess a comprehensive understanding of these three factors, as concluded. Keywords: Price; Service Quality; Customer Satisfaction; Customer Loyalty